Dinamika Efisiensi Pasar dan Kompleksitas Struktural Pada Pasar Saham dan Cryptocurrency - Mahyudin, Roja Putera; Usmany, Alfrin Ernest Marthen (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2025)
This research aims to analyze the dynamics of market efficiency and structural complexity in traditional capital markets and digital asset markets through an econophysics approach. Utilizing the Multifractal Detrended Fluctuation Analysis (MFDFA) integrated with Empirical Mode Decomposition (EMD), this study examines daily data from the S&P 500, NASDAQ, Bitcoin, and Ethereum indices spanning from 2010 to 2024. The analytical results indicate that all tested assets are in a state of structural inefficiency, characterized by drastic variations in the generalized Hurst exponent (h(q))across various fluctuation orders. Although stock indices exhibit an average Hurst value near 0.5, the extreme singularity spectrum width (∆α > 0.8) proves the existence of non-linear scaling laws that reject the Efficient Market Hypothesis (EMH). Digital assets, particularly Bitcoin, demonstrate the highest degree of multifractality (∆α = 0.9352) and strong persistence (H = 0.5581), indicating the dominance of long-term memory and high sensitivity to speculation. These findings confirm the existence of